VATS special issue dedicated to the 4th International VATS Symposium - Scarci, Marco; Crisci, Roberto (Video-Assisted Thoracic Surgery, 2017)
Professor Crisci and I have the great pleasure to introduce you to this special issue. It has been authored by prominent surgeons and it summarise all the topics discussed during the 4th International VATS Symposium in London.